AGROWISATA SINGKONG DESA CINDAI ALUS MARTAPURA - Yuniasari Yuniasari; Dila Nadya Andini (ULM Press, 2021)
Apart from the fishery sector, Cindai Alus Village also has other potentials namely in the cassava plantation sector and its process products. However, it is not widely known by the community due to the lack of special attention and supporting facilities. Cassava Agrotourism in Cindai Alus, Martapura Village is a facility to introduce and raise to introduce and raise the potential of Cindai Alus Village in the cassava plantation sector and its processed products to the wider community. Agritourism was designed with the main aim of attracting tourist visit through the tourist attraction processing approach so as to produce the facilities needed by tourists. Then, to optimize the context of cassava plantation land, the concept of “cassava stage” was applied to produce an agritourism design that is distinctive and memorable for tourists.